Keefektifan Konseling Kelompok Dengan Teknik Strength Bombardment Untuk Meningkatkan Motivasi Belajar Pasca Pandemi Pada Mahasiswa - Adetea Juliza H; Suryati Suryati; Hartika Utami Fitri (Journal of Society Counseling, 2023)
This research examines "the effectiveness of group counseling using the strength bombardment technique to increase post-pandemic learning motivation in college students". This study aims to describe the level of learning motivation of students in the Islamic guidance and counseling study program, and to help students with low learning motivation. This study used a quasi-experimental method with a total population of 139 people and a sample of 34 respondents. Sampling using purposive sampling technique, with a total of 12 respondents. Data collection techniques using questionnaires and documentation. The data analysis technique used the Wilcoxon test with the help of SPSS version 23. The results showed that the post-pandemic level of student learning motivation was in the moderate category of 74%, and the results of the Wilcoxon test showed a Z score (-3,088) with a value of 0.002 <0.05. It can be concluded that is accepted and is rejected, so that the implementation and application of group counseling using the strength bombardment technique is effective for increasing post-pandemic learning motivation in students.